Understanding the Mechanism of Lithium Ion Extraction Using Tributyl Phosphate in Room Temperature Ionic Liquid. Issue 7 (9th November 2020) - Masmoudi, Abderrazak; Zante, Guillaume; Trébouet, Dominique; Barillon, Rémi; Boltoeva, Maria
ABSTRACT: This paper reports the liquid-liquid extraction behavior of lithium ions from aqueous solutions containing hydrochloric acid using a well-known neutral extractant tri- n -butyl phosphate (TBP) and commonly used imidazolium-based ionic liquids (IL). The effect of several experimental parameters on the lithium partitioning was examined, in particular the nature of counter anions, the concentration of TBP, the pH of the aqueous solutions, and the initial lithium ion concentration. The lithium extraction was also investigated with a conventional organic solvent 1-octanol to understand the role of the IL in the extraction process. Our results suggest that lithium partition into TBP/IL system proceeds via two mechanisms, namely by cationic exchange and ion pair transfer. The corresponding extraction equilibrium constants as well as stoichiometry of extracted complexes were determined. To overcome the loss of ionic liquid by cation exchange, we have shown that TBP mixed with an ionic liquid possessing low solubility in aqueous phases can extract lithium when a highly hydrophobic counter-ion such as ( T f 2 N − ) is present in the aqueous phase.